"English for Academic Purposes in the Korean University Context: Teachers’ Opinions on What is Being Taught, How it is Being Taught, and Possible Improvements" - Kobylinski, Chris; Prasad, Richard (International Journal of Educational Technology and Learning, 2018)
As the use of English in the academic world increases around the world, English for Academic Purposes (EAP) continues to grow. The increase in demand for EAP courses and teachers often finds English teachers having to prepare students to study in fields that they themselves might not be familiar with or teach a style of course they might not have done before. In addition to these obstacles, there are many institutional barriers that prevent teachers from teaching EAP properly. This paper examines these problems in the South Korean university context. Currently many Native English Speaking (NES) English teachers are transitioning from teaching Commutative Language Teaching (CLT) classes to teaching EAP courses and are experiencing many problems and barriers as they transition and teach EAP. 10 NES university teachers were interviewed in order to gather qualitative data about their experiences in teaching EAP courses in an attempt to better understand the current situation in many Korean universities. The data gathered revealed many similar problems and led to ideas for possible improvement on many levels.